2016
DOI: 10.1097/mnh.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels in primary cilia

Abstract: Purpose of review Primary cilia have become important organelles implicated in embryonic development, organogenesis, health, and diseases. While many studies in cell biology have focused on changes in ciliary length or ciliogenesis, the most common readout for evaluating ciliary function is intracellular calcium. Recent findings Recent tools have allowed us to examine intracellular calcium in more precise locations, i.e. the cilioplasm and cytoplasm. Advances in calcium imaging have also allowed us to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 80 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…One possibility would be that β-cells possess Ca 2+ channels on their ciliary membrane (63) and that ciliary Ca 2+ fluxes serve as gatekeepers of cytosolic Ca 2+ . Alternately, the cilia may relay signals from ambient stimuli to open Ca 2+ channels on the plasma membrane (64,65). It would be prudent to test these scenarios in both mouse and human β-cells, as there exist considerable differences in their Ca 2+ channel expression, distribution, and activation (66).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility would be that β-cells possess Ca 2+ channels on their ciliary membrane (63) and that ciliary Ca 2+ fluxes serve as gatekeepers of cytosolic Ca 2+ . Alternately, the cilia may relay signals from ambient stimuli to open Ca 2+ channels on the plasma membrane (64,65). It would be prudent to test these scenarios in both mouse and human β-cells, as there exist considerable differences in their Ca 2+ channel expression, distribution, and activation (66).…”
Section: Discussionmentioning
confidence: 99%
“…The cascading Ca 2+ currents typically observed after glucose stimulation were abolished in the cilia-less βCKO line, leading to impaired insulin secretion, which established that glucose-mediated Ca 2+ oscillations are cilia-dependent [ 118 ]. While the exact mechanism of Ca 2+ regulation by β-cell primary cilium is unclear, the existence of Ca 2+ channels on the ciliary membrane, as well as the Ca 2+ -fluxes serving as moderators of cytosolic Ca 2+ levels are strong evidence of its vital role in glucose-mediated insulin secretion [ 11 , 42 , 121 ].…”
Section: Cilia-mediated and Calcium-dependent Biological Processesmentioning
confidence: 99%
“…High levels of Ca 2+ -permeable channels, such as polycystin 2 (PC-2) and transient receptor potential cation channel subfamily V member 4 (TRPV4), are present on both the ciliary membrane and basal body; the intracellular anchor point the cilium originates from [ 10 ]. It is generally believed that an influx of extracellular Ca 2+ into the primary cilia precedes a rise in cytosolic Ca 2+ ; however, the exact mechanism by which this happens remains unknown [ 11 , 12 , 13 , 14 , 15 , 16 ]. To further complicate things, there may not be a uniform mechanism explaining ciliary Ca 2+ signaling but one that is instead cell-type specific, as the type of Ca 2+ channels and ciliary activation pathways vary by cell type.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers reported that cilia-specific calcium influx did not occur in response to fluid flow, even when supraphysiological fluid flows were applied 30 . These results suggest that mechanosensation by the primary cilium might be independent of ciliary calcium signaling 30 ; however, potential technical issues such as oversaturation of the calcium reporter due to a relatively high calcium concentration in the primary cilium might complicate the interpretation of these data 63 . In fact, several other reports support the increase in ciliary calcium in response to mechanical stimuli in cultured renal cells [64][65][66][67] .…”
Section: [H2] Mechanosensing By the Primary Ciliummentioning
confidence: 91%